Appreciating the Multiple Processes Increasing Individual or Population Fitness. (May 2019) - Edelaar, Pim; Bolnick, Daniel I.
Abstract : Natural selection results in adaptation for populations, not individuals. Yet environmental change can reduce the expected fitness of an individual. Selection will favor the evolution of traits that allow individuals to proactively compensate for such reduced fitness. Although several well-known processes can achieve this goal, they are still often neglected and often not clearly distinguished. To facilitate greater attention to the full range of processes by which individuals can increase their fitness, we present a classification scheme that integrates these: phenotypic change, selection of the environment, and adjustment of the environment. We outline how these individual-level processes relate to natural selection and population-level fitness. This framework may help to guide research (and teaching) about how individuals and populations may respond to environmental change. Highlights: Individuals and populations can increase their fitness in at least four distinct ways. We place these processes in a classifying framework that highlights their similarities and differences. This is based on what changes (the phenotypic trait or the environment) and how it changes (via alteration or via selection). The framework places major stress on the ability of individuals to adaptively change their environments, via 'adjustment of their environment' and 'selection of their environment'. While the distinct processes are not new, some are frequently confused or overlooked. The framework is valid for any ecological context (including sexual and social). It therefore has the potential to be applicable to any research field and to draw attention to underexplored research topics. In particular, little is known about the relative contributions of the four processes to adaptation and how they interact.